2010
DOI: 10.1089/scd.2009.0458
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Induced Pluripotent Stem Cells Produce Chimeric Offspring

Abstract: Ethical and moral issues rule out the use of human induced pluripotent stem cells (iPSCs) in chimera studies that would determine the full extent of their reprogrammed state, instead relying on less rigorous assays such as teratoma formation and differentiated cell types. To date, only mouse iPSC lines are known to be truly pluripotent. However, initial mouse iPSC lines failed to form chimeric offspring, but did generate teratomas and differentiated embryoid bodies, and thus these specific iPSC lines were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
228
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(237 citation statements)
references
References 58 publications
5
228
1
3
Order By: Relevance
“…However, the results showed that AZA alone had no significant improvement on reprogramming whereas VPA treatment significantly increased the expression of pluripotent genes and accelerated the reprogramming. Consistent with previous reports, treatment of AZA showed no effect on PEF reprogramming (Esteban et al 2009); moreover, the effect of VPA on reprogramming might be due to the collective effects of upregulation of pluripotentspecific genes (Huangfu et al 2008, West et al 2010.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the results showed that AZA alone had no significant improvement on reprogramming whereas VPA treatment significantly increased the expression of pluripotent genes and accelerated the reprogramming. Consistent with previous reports, treatment of AZA showed no effect on PEF reprogramming (Esteban et al 2009); moreover, the effect of VPA on reprogramming might be due to the collective effects of upregulation of pluripotentspecific genes (Huangfu et al 2008, West et al 2010.…”
Section: Discussionsupporting
confidence: 91%
“…Despite intensive efforts by multiple groups over several years, the characteristics of pig iPS cells, including their morphology, surface markers, and pluripotency, had not been distinctly documented and remain controversial (Esteban et al 2009, Ezashi et al 2009, West et al 2010. Pig iPS cells provide a feasible platform to generate the pluripotent cells or germ layer-specific progenitors, which might be useful in differentiating in vitro or the precise genetic engineering in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Although three groups announced recently they had established iPSCs in pig by introduced human or mouse derived transcriptional factors (Oct4, Sox2, Klf4, and C-myc), none of them successfully applied the iPSCs in generating chimeras, which is the basic standard to define pluripotency (Esteban et al, 2009;Ezashi et al, 2009;Wu et al, 2009). Only one report showed that porcine mesenchymal stem cells (MSCs) transduced with six human transcription factors (Nanog,Oct4, Sox2, Klf4, C-myc, and Lin28) could generate chimeras and suggested the insufficient endogenous Nanog expression may be responsible for the failure of generating chimeras (West et al, 2010). A recent report also mentioned that pig iPSCs generated by six genes had higher percentage of undifferentiated colonies during the early passages .…”
Section: Introductionmentioning
confidence: 99%
“…For example, pig iPSCs do not exhibit as robust reactivation of endogenous pluripotency genes as mouse iPSCs, and they are incapable of silencing integrated genes (Esteban et al, 2009;Ezashi et al, 2009;Wu et al, 2009). Nevertheless, porcine iPSCs derived from mesenchymal cells are capable of contribution to all three germ layers after injection into the early embryo, affirming that they at least are capable of multilineage differentiation (West et al, 2010).…”
Section: Reprogramming With Different Factors Of Transcription Factorsmentioning
confidence: 91%
“…Through iterative experiments, they eventually found that all factors save four were dispensable for reprogramming-these four factors became known as the classical quartet of pluripotential reprogramming factors; Oct4, Sox2, Klf4, and c-Myc (Takahashi and Yamanaka, 2006). This classical cocktail of reprogramming factors has been shown to induce pluripotency within a multitude of mouse cell types, as well as rhesus monkey (Li et al, 2009b;Liao et al, 2009), pig (Esteban et al, 2009;Ezashi et al, 2009;Wu et al, 2009;West et al, 2010) and human cells (Takahashi et al, 2007;Yamanaka, 2007).…”
Section: Reprogramming With Different Factors Of Transcription Factorsmentioning
confidence: 99%